The rigor of a certain inhumanity : toward a wider suffrage - Llewelyn, John, 1928- (Studies in Continental thought., 2012)
Focusing on the idea of universal suffrage, John Llewelyn accepts the challenge of Derrida's later thought to renew his focus on the ethical, political, and religious dimensions of what makes us uniquely human. Llewelyn builds this concern on issues of representation, language, meaning, and logic with reflections on the phenomenological figures who informed Derrida's concept of deconstruction. By entering into dialogue with these philosophical traditions, Llewelyn demonstrates the range and depth of his own original thinking. The Rigor of a Certain Inhumanity is a rich and passionate, playful.